Association of LDL-C/HDL-C Ratio With Stroke Outcomes Within 1 Year After Onset: A Hospital-Based Follow-Up Study - Liu, Li; Yin, Ping; Lu, Chong; Li, Jingxin; Zang, Zhaoxia; Liu, Yongdan; Liu, Shuang; Wei, Yafen (Frontiers in Neurology, 2020)
Stroke remains a leading cause of death and disability. The low-density lipoprotein cholesterol to high-density lipoprotein cholesterol (LDL-C/HDL-C ratio) ratio has been confirmed to be a predictor of stroke. However, few studies have assessed the prognostic impact of the LDL-C/HDL-C ratio for stroke patients. We aimed to investigate the relationship between the LDL-C/HDL-C ratio and the prognosis following stroke in Chinese patients. A total of 3410 patients who had experienced their first ischemic stroke was recruited to this study within 72 hours of stroke onset. The patients were followed for at least 12 months. A multivariate regression analysis was used to assess the association between the LDL-C/HDL-C ratio and prognosis following stroke. We considered the LDL-C/HDL-C ratio as a continuous variable and stratified patients according to the LDL-C/HDL-C ratio quartile. A higher LDL-C/HDL-C ratio was associated with lower rates of death, recurrence, and moderate disability (defined as a modified Rankin scale score >2) at 3 months. Using group 1 as the reference group, the relative risk (RRs) at 3 months for death were 0.45 (95% confidence interval [CI]: 0.27, 0.77) for group 2, 0.58 (95% CI: 0.34, 0.98) for group 3, and 0.97 (95% CI: 0.60, 1.56) for group 4; for recurrence, the RRs were 0.75 (95% CI: 0.56, 0.99) for group 2, 0.65 (95% CI: 0.48, 0.89) for group 3, and 0.55 (95% CI: 0.39, 0.78) for group 4; and for moderate disability, the RRs were 0.74 (95% CI: 0.55, 0.99) for group 2, 0.65 (95% CI: 0.47, 0.89) for group 3, and 0.55 (95% CI: 0.39, 0.77) for group 4. At 12 months, patients in group 2 were the most protected against ischemic stroke death (RR: 0.57; 95% CI: 0.34, 0.95). However, there were no associations between the LDL-C/HDL-C ratio and stroke recurrence or moderate disability. A higher LDL-C/HDL-C ratio was found to protect against death, recurrence, and moderate disability at 3 months. However, there was no significant association between the LDL-C/HDL-C ratio and stroke recurrence or moderate disability at 12 months. These results nonetheless suggest that a higher LDL-C/HDL-C ratio was associated with short-term stroke prognosis.